2022
DOI: 10.1021/acs.chemmater.2c00608
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Structural Disorder to Li+ Ion Transport in Li4–xGe1–xSbxS4 (0 ≤ x ≤ 0.2)

Abstract: Strong compositional influences are known to affect the ionic transport within the thio-LISICON family; however, a deeper understanding of the resulting structure–transport correlations has up until now been lacking. Employing a combination of high-resolution neutron diffraction, impedance spectroscopy, and nuclear magnetic resonance spectroscopy, together with bond valence site energy calculations and the maximum entropy method for determining the underlying Li+ scattering density distribution of a crystal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
(162 reference statements)
2
8
0
1
Order By: Relevance
“…In this work, Sb 5+ was chosen to substitute Ge 4+ in the structure of Li 4 GeS 4 to form a series of solid solutions Li 4– x Ge 1– x Sb x S 4 (0 ≤ x ≤ 0.75), which can induce Li-ion vacancies and facilitate Li-ion diffusion. ,,, Evolution of the crystal structure, ionic conductivity, and diffusion barrier energy in the series were investigated using the powder X-ray Rietveld refinement, ionic conductivity measurements, and bond valence site energy (BVSE) calculations. In the course of the present work, Helm et al reported the same substitution series with x values up to 0.2; in that study, the highest ionic conductivity was found for x = 0.09, showing 2.2 × 10 –5 S cm –1 at room temperature . In our case, we prepared phases with an extended substitution level up to x = 0.75 and obtained an order of magnitude higher ionic conductivity of 1.23 × 10 –4 S cm –1 for Li 3.68 Ge 0.69 Sb 0.31 S 4 (LGSbS-04), a material that also showed an enhanced air stability [a relative humidity (R.H.) of 15% at 303 K] compared to Li 3 PS 4 .…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…In this work, Sb 5+ was chosen to substitute Ge 4+ in the structure of Li 4 GeS 4 to form a series of solid solutions Li 4– x Ge 1– x Sb x S 4 (0 ≤ x ≤ 0.75), which can induce Li-ion vacancies and facilitate Li-ion diffusion. ,,, Evolution of the crystal structure, ionic conductivity, and diffusion barrier energy in the series were investigated using the powder X-ray Rietveld refinement, ionic conductivity measurements, and bond valence site energy (BVSE) calculations. In the course of the present work, Helm et al reported the same substitution series with x values up to 0.2; in that study, the highest ionic conductivity was found for x = 0.09, showing 2.2 × 10 –5 S cm –1 at room temperature . In our case, we prepared phases with an extended substitution level up to x = 0.75 and obtained an order of magnitude higher ionic conductivity of 1.23 × 10 –4 S cm –1 for Li 3.68 Ge 0.69 Sb 0.31 S 4 (LGSbS-04), a material that also showed an enhanced air stability [a relative humidity (R.H.) of 15% at 303 K] compared to Li 3 PS 4 .…”
Section: Introductionsupporting
confidence: 72%
“…The Rietveld refinement results for the phases of x = 0.1, 0.25, and 0.333 are shown in the Supporting Information (Figures S8–S10 and Tables S2–S4). Recently, Helm et al found an additional lithium site [Li(4)] when Sb was substituted for Ge, which was confirmed by neutron diffraction . However, due to the low scattering power of Li atoms in XRD, which was only available under our circumstances, refinement including the Li(4) site was unstable in the present work.…”
Section: Resultsmentioning
confidence: 47%
See 2 more Smart Citations
“…Demnach steigern die durch den Einbau bedingten Strukturänderungen die Konfigurationsentropie und damit auch die ionische Leitfähigkeit um bis zu zwei Größenordnungen (2,4 × 10 -7 S•cm -1 für Li 4 [GeS 4 ], 2,2 × 10 -5 S•cm -1 für Li 3,91 Ge 0,91 Sb 0,09 S 4 ). 2) Fässler, van Wüllen und Mitarbeitende berichteten über drei neue Hochtemperaturmodifikatio-nen der Lithiumphosphidotrielate ω-Li 9 [TrP 4 ] (Tr Al, Ga, In), die Li + -Ionenleitfähigkeiten von bis zu 4,5 mS • cm -1 bei Raumtemperatur zeigen (Abbildung 1). 3) Durch Experimente und quantenchemische Methoden erklären sie diese Beobachtung und korrelieren die Leitfähigkeit mit der Struktur.…”
Section: Batterienmit Lithium Und Natriumunclassified